Study on pathogenicity of Orf virus strain UPM 1/14 Malaysia and UPM 2/14 Malaysia in rats via different inoculation sites with and without dexamethasone treatment - Chook, Chian Lin (2016)
In this study, pathogenicity of ORFV in rat was evaluated by using of two virus strains, ORFV UPM 1/14 Malaysia and ORFV UPM 2/14 Malaysia with variation in inoculation sites and the effects of induced-immunosuppression. Intradermal inoculation of 0.5 ml 1% ORFV UPM 1/14 Malaysia ( Group 1 ) and ORFV UPM 2/14 Malaysia virus suspension ( Group 2 ) were performed in each group of 5 rats in Group 1 and Group 2 at dorsum ( Group 1A; Group 2A ), ear pinna ( Group 1B; Group 2B ) and labial commissure ( Group 1C; Group 2C ) respectively. Intradermal inoculation of 0.5 ml 1% ORFV UPM 1/14 Malaysia virus suspension was performed in dexamethasone-induced immunosuppressed group ( n=5 ) and non dexamethasone group ( n=5 ). Clinical signs and histopathological changes were evaluated for 14 days post virus inoculation for rats in Group 1 and Group 2 and 7 days for dexamethasone-induced immunosuppressed group and non-dexamethasone group. Mild hyperemia was observed in dorsum, ear pinna and labial commissure of 27 rats in the treatment group. Rats of Group 1 had significantly higher ( p<0.05 ) mean skin lesion scores than Group 2. Rats of Group 1A had significantly higher ( p<0.05 ) mean skin lesion scores than Group 1B and Group 1C. Dexamethasone treated group had significantly higher ( p<0.05) mean skin lesion scores than non dexamethasone group. Keratosis, acanthosis and ballooning degeneration were observed in rats showed skin lesions in the treatment group. Dexamethasone-treated group had significantly higher ( p<0.05 ) mean thickness of stratum spinosum and stratum basale of labial commissure than non-dexamethasone group. There was no significant difference ( p>0.05 ) of mean thickness of stratum spinosum and stratum basale of dorsum, ear pinna and labial commissure between Group 1 and Group 2. ORFV was detected by means of PCR on skin tissues of rats with skin lesions in rats. In conclusion, ORFV is pathogenic in rats, and it varies due to strains, inoculation sites and dexamethasone treatment. Disease and lesions produced in rats are similar to that of the normal hosts. Thus, rat is a suitable laboratory animal model to study OFRV infection.